Contextual appraisal of GM cotton diffusion in South Africa - (:unkn) unknown (My University, 2007)
The bulk of the South African cotton crop is produced by large scale commercial farmers. Therefore it might be misleading to present South Africa's impressive Genetically Modified Cotton (GMC) adoption figures as evidence of successful GMC use by smallholder farmers. The South African cotton sector struggles in an unstable production and market environment and smallholders with limited resources and limited production, managerial and marketing capacity and choice suffer most. The total South African cotton area and number of farmers decreased drastically since the introduction of GMC and this causes observers to question the so-called success story of GMC in South Africa. The South African smallholder experience has shown that technology introduction on its own cannot sustainably increase production; factors like institutional arrangements plays a vital role. Studies have in the past focussed exclusively on the performance of the new technology and the institutional role has been under emphasised. The results of our research complement the existing studies by pointing out low profitability in an unfavourable climatic and institutional context. This reminds us that rain-fed agriculture remains sensitive to climatic hazards and that new technology adoption under these conditions might increase financial risk associated with cotton production.
Keywords: African Research